2013
DOI: 10.1111/jvim.12248
|View full text |Cite
|
Sign up to set email alerts
|

Focal Intestinal Lipogranulomatous Lymphangitis in 6 Dogs (2008–2011)

Abstract: BackgroundLipogranulomatous lymphangitis is inflammation of the intestinal lymphatic vessels and surrounding tissues caused by chronic leakage of lipid‐laden chyle. Grossly, lipogranulomas are typically disseminated small masses on the serosa and surrounding lymphatic vessels and consist of epithelioid macrophages, multinucleated giant cells, and cholesterol. Lipogranulomatous lymphangitis is occasionally seen in patients with lymphangiectasia and protein‐losing enteropathy (PLE).ObjectivesTo characterize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 7 publications
5
42
0
Order By: Relevance
“…Considering that dogs with primary IL tend to be young and responsive to ULFD, we speculate that the dogs with FR‐PLE in our study in fact may have had primary IL even though not every responder showed lacteal dilatation on histopathology. Considering the limitations of endoscopic tissue biopsy samples for the diagnosis of IL, structural lesions might have been present in the deeper mucosa or distal jejunum, or might have been artificially altered during the collection, which may have led to an underestimation of IL . These findings are supported by the fact that the majority of the dogs in the FR‐PLE group in our study (22 of the 23, 95.7%) had intestinal hyperechoic mucosal striations.…”
Section: Discussionsupporting
confidence: 64%
“…Considering that dogs with primary IL tend to be young and responsive to ULFD, we speculate that the dogs with FR‐PLE in our study in fact may have had primary IL even though not every responder showed lacteal dilatation on histopathology. Considering the limitations of endoscopic tissue biopsy samples for the diagnosis of IL, structural lesions might have been present in the deeper mucosa or distal jejunum, or might have been artificially altered during the collection, which may have led to an underestimation of IL . These findings are supported by the fact that the majority of the dogs in the FR‐PLE group in our study (22 of the 23, 95.7%) had intestinal hyperechoic mucosal striations.…”
Section: Discussionsupporting
confidence: 64%
“…, Watson et al . ). Differential diagnoses usually include neoplastic and non‐neoplastic causes of intestinal masses such as infectious granulomatous disease (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…, Watson et al . ). The aetiology is unclear and the prognosis is guarded (Guilford ), although long‐term remission can be achieved following surgical excision of the lesion (Watson et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations